1452. A Clinico-Epidemiological Study of Childhood Herpes Zoster. (15th December 2022) - Mitra, Barnali; Mitra, Debdeep
Abstract: Background: Herpes Zoster (HZ) is a viral infection believed to be due to re-activation of Varicella zoster virus (VZV) or human herpesvirus type 3 (HHV-3) that persists in the posterior nerve root ganglion. HZ is rarely reported in the pediatric age group with an intact immunity. Past infection with VZV and immunization with chicken pox vaccine are key markers in the onset of varicella zoster in children. Methods: A prospective observational study over a total duration of two years was conducted in a tertiary hospital and all children less than 12 years of age with diagnosed HZ were included in the study. Herpes zoster in a 2 years old child Herpes zoster in a 11 years old child Results: A total of 39 children were diagnosed to have pediatric HZ infection during the study period of two years. The children were followed up over 4 weeks post diagnosis and treated with oral Acyclovir therapy along with symptomatic management. All the children had an uneventful benign course and their siblings and close pediatric contacts were also screened for the development of HZ or chicken pox during the incubation period. All children were screened for an underlying immunodeficiency, and two cases of HIV co-infection was detected. Tzank smear Skin biopsy Conclusion: HZ is a rare disease in childhood. Varicella in early childhood is a risk factor of HZ in immunocompromised and immunocompetent children. Childhood zoster occurs in either healthy or underlying immunodeficient children. The appearance of HZ in a young child does not always imply an underlying immunodeficiency or malignancy but the children should be screened for immunodeficiency. The prognosis is generally good in healthy children. Disclosures: All Authors : No reported disclosures.